The Efficacy of Mirabegron in Medical Expulsive Therapy for Ureteral Stones: A Systematic Review and Meta-Analysis. (24th March 2022) - Cai, Dawei; Wei, Guangzhu; Wu, Peishan; Huang, Yongjin; Che, Xuanyan; Zhang, Yong; Zhou, Zhongbao; Kong, Guangqi
Abstract : Background . This study aimed to assess the efficacy of mirabegron (50 mg daily) as a medical expulsive therapy for ureteral stones in adults. Materials and Methods . We searched PubMed, Embase, Cochrane Library, and Web of Science from inception to July 2021 to collect the clinical trials. Two reviewers independently screened literature, extracted data, and assessed the risk of bias of included studies by using the Cochrane risk of bias tool. Review Manager 5.3 software was used for the meta-analysis. Results . A total of four studies were included, involving 398 patients: 197 patients in mirabegron group and 201 patients in control group. The meta-analysis showed that the stone expulsion rate was higher in the mirabegron group than in the control group (OR: 2.12; 95% CI: 1.33 to 3.40; p = 0.002 ). Subgroup analysis identified that the stone expulsion rate of patients with stone size <5/6 mm was significantly higher than that of patients with stone size ≥5/6 mm (OR: 0.31; 95% CI: 0.13 to 0.72; p = 0.006 ). But no significant difference was identified between the mirabegron group and the control group for the stone expulsion interval (MD: −1.16, 95% CI: −3.56 to 1.24; p = 0.35 ). In terms of pain episodes, the mirabegron group was significantly lower than that of the control group (MD: −0.34, 95% CI: −0.50 to 0.19; p < 0.0001 ). Conclusions . The medical expulsive therapy with mirabegron had a significant effect in improving the stone expulsion rate for patients with ureteral stones, especially in those whose stone size <5/6 mm. Mirabegron had no effect on the stone expulsion interval but did decrease the pain episodes.